2005
DOI: 10.1158/0008-5472.can-05-0205
|View full text |Cite
|
Sign up to set email alerts
|

4-(Methylnitrosamino)-1-(3-Pyridyl)-1-Butanone from Cigarette Smoke Stimulates Colon Cancer Growth via β-Adrenoceptors

Abstract: Cigarette smoking is a risk factor for colorectal cancer. It is suggested that 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), a tobacco-specific nitrosamine, mediates the carcinogenic action of cigarette smoking by promoting cancer growth. In the present study, the proliferative response of a cultured colon cancer cell line HT-29 to NNK was determined. It was found that NNK dose-dependently stimulated HT-29 cell proliferation. In this regard, the stimulatory action of NNK was abolished by atenolol and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
98
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 29 publications
11
98
0
Order By: Relevance
“…One of the traditional G-proteindependent signaling pathways by β2AR is to activate ERK, which is the fast response signal after Iso stimulation (18). In the present investigation, we provide evidence that β2AR activation promotes prostate cancer cell proliferation and cell migration, through increasing cancer cellular cAMP level and ERK activation, further supporting that increased cAMP levels and ERK activation are involved in the β2AR-activated cell progression (14,19).…”
Section: Discussionsupporting
confidence: 72%
“…One of the traditional G-proteindependent signaling pathways by β2AR is to activate ERK, which is the fast response signal after Iso stimulation (18). In the present investigation, we provide evidence that β2AR activation promotes prostate cancer cell proliferation and cell migration, through increasing cancer cellular cAMP level and ERK activation, further supporting that increased cAMP levels and ERK activation are involved in the β2AR-activated cell progression (14,19).…”
Section: Discussionsupporting
confidence: 72%
“…25,26). Other reports have shown that NNK-induced h-adrenergic signaling was associated with cell survival and growth regulation in several other nonsmall-cell and small-cell lung cancer cell lines and in colon cancer cells (27,28).…”
Section: Introductionmentioning
confidence: 87%
“…4,5 β-adrenoceptors, which are members of the G-proteincoupled receptor (GPCR) superfamily, can regulate tumor proliferation and are involved in cancer development. [6][7][8][9] Recent studies have shown that cell lines derived from human pancreatic tumors express high levels of β 1 -and β 2 -adrenoceptors. 4,10 The nicotine-derived nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) resembles a β-adrenergic β 2 -adrenergic antagonists suppress pancreatic cancer cell invasion by inhibiting CREB, NFκB and AP-1 β 2 -adrenoceptors in human pancreatic cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%